Considerations of dopant-dependent bandgap narrowing for accurate device simulation in abrupt HBTs - 周守利 熊德平 覃亚丽 (Journal of semiconductors, 2009)
Heavy doping of the base in HBTs brings about a bandgap narrowing （BGN） effect, which modifies the intrinsic carrier density and disturbs the band offset, and thus leads to the change of the currents. Based on a thermionic-field-diffusion model that is used to the analyze the performance of an abrupt HBT with a heavydoped base, the conclusion is made that, although the BGN effect makes the currents obviously change due to the modification of the intrinsic carrier density, the band offsets disturbed by the BGN effect should also be taken into account in the analysis of the electrical characteristics of abrupt HBTs. In addition, the BGN effect changes the bias voltage for the onset of Kirk effects.